Gualou Guizhi Granule Protects against OGD/R-Induced Injury by Inhibiting Cell Pyroptosis via the PI3K/Akt Signaling Pathway. (8th March 2021) - Zhang, Yuqin; Wang, Hongyun; Li, Huang; Nan, Lihong; Xu, Wei; Lin, Yu; Chu, Kedan
Abstract : Pyroptosis is a proinflammatory form of regulated cell death that plays an important role in ischemic stroke. Gualou Guizhi granule (GLGZG) is a classic prescription that has been shown to exert neuroprotective effects against cerebral ischemia reperfusion injury. In the present study, we examined the involvement of pyroptosis and its associated mechanism in protecting nerve function. Methods . Primary neurons were exposed to oxygen-glucose deprivation and reperfusion (OGD/R) conditions in the presence or absence of GLGZG. Cellular viability was measured by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazoliumbromide (MTT) assay. The number of apoptoic cells was detected by NeuN and NSE protein expression. The expression levels of the pyroptosis markers, namely, NOD-like receptor family pyrin domain-containing 3 (NLRP3), apoptosis-associated speck-like protein containing a CARD (ASC), caspase-1, interleukin-18 (IL-18), and IL-1 β were determined by quantitative real-time PCR analysis, western blot, and ELISA analyses as appropriate. Moreover, the expression levels of the PI3K/Akt pathway key proteins were determined by quantitative real-time PCR analysis and western blot assays. To determine the PI3K/Akt pathway involvement in GLGZG-mediated neuroprotection, the PI3K inhibitor LY294002 (LY, 10  μ M) was added. The expression levels of NeuN, Akt, and p-Akt were evaluated. Results . It was found that GLGZG could inhibit OGD/R-induced cell apoptosis, increase neuronal cell viability, decrease the production of IL-18 and IL-1 β, and downregulate the expression levels of pyroptosis markers (NLRP3, ASC, and caspase-1). Furthermore, GLGZG could modulate the PI3K/Akt signaling pathway. Pharmacological inhibition of the PI3K pathway not only abrogated the effects of GLGZG on Akt but also neutralized its prosurvival and antipyroptotic actions. Conclusions . The findings indicated that GLGZG pretreatment effectively reduced OGD/R-induced injury by inhibiting cell pyroptosis and activating the PI3K/Akt pathway. These data provide important evidence for the therapeutic applications of this regimen in ischemic stroke.